Elucidating the Effects of Formalin as Food Preservative on Hematological Profile and Fertility of Swiss Albino Mice (Journal of Science and Technology Research, 2024)
In Bangladesh, the use of formalin as a food preservative has recently expanded significantly. With this backdrop, the study was attempted to discover changes in the fertility, gross structure, and histoarchitecture of the male reproductive system and hematology in Swiss albino mice as a result of formalin use. Up until experimental week 24, four groups of four mice each were given normal drinking water mixed with formalin at doses of 1%, 5%, 10%, and 20%, respectively, orally. A control group of mice (n=4) were given normal drinking water only. After 24 weeks of treatment, the testicular weight, sperm concentration, morphology, gonadosomatic index (GSI), and hematological profile were evaluated. Testicular histological changes were also evaluated. Formalin-treated mice had significantly lower testes weight, GSI, and sperm count (P